2003
DOI: 10.1007/s10267-003-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Conidium morphology of Curvularia geniculata and allied species

Abstract: The species delimitation of some members of Curvularia with 4-septate conidia was studied. Conidial shapes and sizes were variable to some extent depending on isolates and herbarium materials examined. By crossing experiments, C. affinis, C. fallax, and C. senegalensis showed no reproductive isolation from C. geniculata. Some isolates obtained from culture collections and from fields were not fertile with tester isolates of C. geniculata. Their conidial morphology were somewhat different from C. geniculata. SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Intraspecific variation within the C. geniculata population Intraspecific variation was found within the C. geniculata population, including groups formerly treated as the separate species C. affinis, C. fallax, and C. senegalensis (Hosokawa et al 2003). Among C. geniculata populations, the maximum intraspecific genetic distance was 0.0137.…”
Section: Brn1 Dna Sequencesmentioning
confidence: 98%
See 3 more Smart Citations
“…Intraspecific variation within the C. geniculata population Intraspecific variation was found within the C. geniculata population, including groups formerly treated as the separate species C. affinis, C. fallax, and C. senegalensis (Hosokawa et al 2003). Among C. geniculata populations, the maximum intraspecific genetic distance was 0.0137.…”
Section: Brn1 Dna Sequencesmentioning
confidence: 98%
“…They were grown on modified V-8 juice agar (Tsuda and Ueyama 1987) or complete agar medium (CM) (Shimizu et al 1997) in slant cultures maintained at 25°C. Conidial morphology of representative isolates was shown in the previous report (Hosokawa et al 2003). Species or isolates with protuberant hilum conidia and C. robusta isolates used in this study are shown in Figs.…”
Section: Isolates and Media Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the above treatments were all based on morphology, and the genus has not been well examined using modern protocols. The classical identification of Cochliobolus and its anamorphs has encountered some problems due to the plasticity of morphological traits under different growth conditions (Old & Roberston, 1969;Hosokawa et al, 2003). We predict that new molecular developments will lead to a rearrangement of taxa at the specific or subspecific level in the near future.…”
Section: Cochliobolus and Its Anamorphsmentioning
confidence: 99%